A 10Be production‐rate calibration for the Arctic. (10th July 2013) - YOUNG, NICOLÁs E.; SCHAEFER, JOERG M.; BRINER, JASON P.; GOEHRING, BRENT M.
ABSTRACT We present a Baffin Bay 10Be production‐rate calibration derived from glacial deposits in western Greenland and Baffin Island, and test our results against published 10Be calibration datasets to develop an Arctic 10Be production rate. Our calibration comprises: (i) 10Be measurements from moraine boulders linked to a 14C‐dated moraine at Jakobshavn Isfjord in western Greenland, (ii) an independent and previously published 10Be production rate at Jakobshavn Isfjord and (iii) re‐measured 10Be concentrations from a Baffin Island calibration site that is included in the north‐eastern North America dataset. Combined, we calculate a sea‐level/high‐latitude 10Be production rate for the Baffin Bay region of 3.96 ± 0.07 atoms g−1 a−1 (Lal/Stone scaling model). After testing the Baffin Bay rate against calibration sites in Norway and north‐eastern North America, we calculate a more conservative Arctic production rate of 3.96 ± 0.15 atoms g−1 a−1. The Baffin Bay and Arctic 10Be production rates are indistinguishable from the north‐eastern North America 10Be production rate (3.91 ± 0.19 atoms g−1 a−1) and yield overall uncertainties of <2–3.7% (1σ). These production rates reduce systematic uncertainties in 10Be‐based chronologies of ice‐margin change and allow 10Be‐based chronologies to be more confidently compared with high‐resolution climate records, such as those from Greenland ice cores.